Arrhythmogenic potential of myocardial disarray in hypertrophic cardiomyopathy: genetic basis, functional consequences and relation to sudden cardiac death. Issue 7 (15th July 2021) - Finocchiaro, Gherardo; Sheikh, Nabeel; Leone, Ornella; Westaby, Joe; Mazzarotto, Francesco; Pantazis, Antonis; Ferrantini, Cecilia; Sacconi, Leonardo; Papadakis, Michael; Sharma, Sanjay; Sheppard, Mary N; Olivotto, Iacopo
Abstract: Myocardial disarray is defined as disorganized cardiomyocyte spatial distribution, with loss of physiological fibre alignment and orientation. Since the first pathological descriptions of hypertrophic cardiomyopathy (HCM), disarray appeared as a typical feature of this condition and sparked vivid debate regarding its specificity to the disease and clinical significance as a diagnostic marker and a risk factor for sudden death. Although much of the controversy surrounding its diagnostic value in HCM persists, it is increasingly recognized that myocardial disarray may be found in physiological contexts and in cardiac conditions different from HCM, raising the possibility that central focus should be placed on its quantity and distribution, rather than a mere presence. While further studies are needed to establish what amount of disarray should be considered as a hallmark of the disease, novel experimental approaches and emerging imaging techniques for the first time allow ex vivo and in vivo characterization of the myocardium to a molecular level. Such advances hold the promise of filling major gaps in our understanding of the functional consequences of myocardial disarray in HCM and specifically on arrhythmogenic propensity and as a risk factor for sudden death. Ultimately, these studies will clarify whether disarray represents a major determinant of the HCM clinical profile, and a potential therapeutic target, as opposed to an intriguing but largely innocent bystander.